First-principles calculations of wurtzite ZnS1-xSex solid solutions for photocatalysis. (December 2019) - Hussain, Sajjad; Guo, Lingju; Louis, Hitler; Zhu, Shuang; He, Tao
Graphical abstract: Bandgap of ZnS1-x Sex solid solutions with suitable energy levels for artificial photosynthesis decreases with increasing Se concentration due to elongation of Se 4p states in valence band. Highlights: Bandgap of ZnS1-x Sex solid solutions decreases with increased Se concentration. Bandgap reduction of ZnS1-x Sex is due to elongation of Se 4p state in valence band. Red shift occurs in peak and edge of optical spectrum with increased Se amount. Photoexcited electron–hole pairs can easily be separated in the solid solutions. Energy levels of ZnS1−x Sex are suitable for reduction/oxidation half reactions. Abstract: In this work, the structural, electronic and optical properties of ZnS1-x Sex solid solutions in wurtzite phase are calculated by using full potential linearized augmented plane wave method. The GGA, HSE06 and mBJ approximations are used to calculate the bandgap values. The calculated mBJ bandgap values are close to the experimental results, which are 3.61, 3.49, 2.84, 2.72 and 2.60 eV for the compounds ZnS, ZnS0.75 Se0.25, ZnS0.5 Se0.5, ZnS0.25 Se0.75 and ZnSe, respectively. The Zn 4 s, Zn 3p, Zn 3d, S 3p and Se 4p states show prominent contribution to the density of states of ZnS1-x Sex solid solutions. The materials show maximum photoresponse in the ultraviolet energy region; while the edges of optical spectra shift to the low energy range with increasing the concentration of Se in the ZnS1-x Sex solid solutions. Calculated effective mass is less than 1.5m0 for all the solid solutions with different Se concentrations, indicating that the ZnS1-x Sex solid solutions exhibit high charge mobility. Furthermore, conduction band minimum (CBM) of the ZnS1−x Sex lies at a more negative value than the CO2 reduction potential and valence band maximum (VBM) is more positive than the water oxidation potential. All these suggest that the ZnS1-x Sex solid solutions are promising for photocatalysis as the catalysts.